Severe and protracted cholestasis in 44 young men taking bodybuilding supplements: assessment of genetic, clinical and chemical risk factors - Stolz, Andrew; Navarro, Victor; Hayashi, Paul H.; Fontana, Robert J.; Barnhart, Huiman X.; Gu, Jiezhun; Chalasani, Naga P.; Vega, Maricruz M.; Bonkovsky, Herbert L.; Seeff, Leonard B.; Serrano, Jose; Avula, Bharathi; et al. (Alimentary pharmacology & therapeutics, 2019)
Summary Background Bodybuilding supplements can cause a profound cholestatic syndrome. Aim To describe the drug‐Induced liver injury network's experience with liver injury due to bodybuilding supplements. Methods Liver injury pattern, severity and outcomes, potential genetic associations, and exposure to anabolic steroids by product analysis were analysed in prospectively enrolled subjects with bodybuilding supplement‐induced liver injury with causality scores of probable or higher. Results Forty‐four males (mean age 33 years) developed liver injury with a median latency of 73 days. Forty‐one per cent presented with hepatocellular pattern of liver injury as defined by the R > 5 ([Fold elevation of ALT] ÷ [Fold elevation of Alk Phos] (mean, range = 6.4, 0.5‐31.4, n = 42) despite all presenting with clinical features of cholestatic liver injury (100% with jaundice and 84% with pruritus). Liver biopsy (59% of subjects) demonstrated a mild hepatitis and profound cholestasis in most without bile duct injury, loss or fibrosis. Seventy‐one per cent were hospitalised, and none died or required liver transplantation. In some, chemical analysis revealed anabolic steroid controlled substances not listed on the label. No enrichment of genetic variants associated with cholestatic syndromes was found, although mutations in ABCB11 (present in up to 20%) were significantly different than in ethnically matched controls. Conclusions Patients with bodybuilding supplements liver injury uniformly presented with cholestatic injury, which slowly resolved. The ingested products often contained anabolic steroids not identified on the label, and no enrichment in genetic variants was found, indicating a need for additional studies.